Sustainable Economic Security and Household Resource Management During Disaster Periods in Southwestern Bangladesh - Shaikh Faisal Shah Ripon; Md. Ahasanullah; Parimal Kumar Karmokar; Shakil Ahmed; Tanbir Hossain (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Economic security is a critical determinant that shapes the socioeconomic resilience of disaster-affected populations, particularly those rendered vulnerable by prolonged economic instability. Objective: This study aims to analyze the role of economic security on resource management factors in southwestern region of Bangladesh. Methods: This study employed Spearman’s rank correlation analysis to examine the relationship between disaster-resilient community conditions and sustainable economic security factors among 200 systematically sampled households in the southwestern region of Bangladesh. Results: The study examined seven sustainable economic security indicators and their correlations with eight disaster-resilient community status variables. Sustainable agricultural practices showed the strongest positive correlation with adaptation capacity (r = 0.845, p < 0.001), while monthly income exhibited a strong negative correlation with informal loan dependency (r = -0.987, p < 0.001). Conclusion: Sustainable agricultural practices, governmental assistance, and housing construction are significantly correlated with enhanced disaster resilience. Income stability reduces dependency on formal and informal loans. Integrated policy frameworks addressing economic security and disaster preparedness are essential for vulnerable coastal communities.